Blockchain networks: Data structures of Bitcoin, Monero, Zcash, Ethereum, Ripple, and Iota. (17th November 2021) - Akcora, Cuneyt Gurcan; Gel, Yulia R.; Kantarcioglu, Murat
Abstract: Blockchain is an emerging technology that has enabled many applications, from cryptocurrencies to digital asset management and supply chains. Due to this surge of popularity, analyzing the data stored on blockchains poses a new critical challenge in data science. To assist data scientists in various analytic tasks for a blockchain, in this tutorial, we provide a systematic and comprehensive overview of the fundamental elements of blockchain network models. We discuss how we can abstract blockchain data as various types of networks and further use such associated network abstractions to reap important insights on blockchains' structure, organization, and functionality. This article is categorized under: Technologies > Data Preprocessing Application Areas > Business and Industry Fundamental Concepts of Data and Knowledge > Data Concepts Fundamental Concepts of Data and Knowledge > Knowledge Representation Abstract : We explain how we can abstract blockchain data as various types of networks and further use such associated network abstractions to reap important insights on blockchains' structure, organization, and functionality.